ANALISIS YURIDIS KONTRAK PENGADAAN BAHAN MAKANAN PASIEN DENGAN METODE PEMILIHAN PENYEDIA SECARA E-PURCHASING ANTARA RUMAH SAKIT â€œXâ€ DENGAN CV â€œYâ€ - Boni Putra; Mahmul Siregar; Syarifah Lisa Andriati (Smart Education, 2025)
Abstract: Implementationofpatientfoodprocurementcontractsusingthe e-purchasingmethodat Hospital X The main focusofthis study isonthree main aspects, namely legal compliance in theimplementationofcontracts, legal protectionforbothpartiesinvolved in thecontract, anddisputeresolutionmechanismsthatcanbetaken in theeventof a breachofcontract. The methodused in this study isnormative legal researchwith a descriptiveanalyticalapproach. This study examineshowlawsandregulations are applied in procurementcontractsthrough e-purchasing. The resultsofthe study The implementationofcontractsthroughthe e-purchasingmethodisconsideredverygood in termsof legal compliance. The partieshavefollowedallgovernmentprocurementprocedures in a transparentandaccountablemanner, sothatthecontractrunseffectivelyandefficiently. The existenceof a cleardisputeresolutionmechanism: The contract has anticipatedpotentialproblems in thefuture, such as breachofcontract. The mechanismsorstepsthatwillbetakentoresolvedisputesiftheyoccurhavebeenclearlyregulated, in accordancewiththecontentsofthecontractandapplicableregulations.Â Â Keyword:E-Purchasing, Procurement Contracts, Legal Compliance, Dispute ResolutionÂ Â Abstrak: Pelaksanaankontrakpengadaanbahanmakananpasienmenggunakanmetode e-purchasing di RumahSakit X Fokusutamapenelitian ini adalahpadatigaaspekutama, yaitukepatuhanhukumdalampelaksanaankontrak, perlindunganhukumbagikeduabelahpihak yang terlibatdalamkontrak, danmekanismepenyelesaiansengketa yang dapatditempuhjikaterjadiwanprestasi. Metode yang digunakandalampenelitianiniadalahpenelitianhukumnormatifdenganpendekatandeskriptifanalitis. Penelitianinimengkajibagaimanaperaturanperundang-undanganditerapkandalamkontrakpengadaanbarangmelaluie-purchasing. Hasil penelitianPelaksanaankontrakmelaluimetodee-purchasingdinilai sangat baikdarisegikepatuhanhukum. Para pihaktelahmengikutisemuaprosedurpengadaanbarang dan jasapemerintahdengantransparan dan akuntabel, sehinggakontrakberjalansecaraefektif dan efisien. Adanya MekanismePenyelesaianSengketa yang Jelas: Kontraktersebutsudahmengantisipasipotensimasalah di kemudianhari, sepertiwanprestasi (pelanggarankontrak). Telah diatursecarajelasmekanismeataulangkah-langkah yang akanditempuhuntukmenyelesaikanperselisihanjikahalituterjadi, sesuaidenganisikontrak dan peraturan yang berlaku.Â Â Kata kunci: E-Purchasing,KontrakPengadaan, Kepatuhan Hukum, PenyelesaianÂ SengketaÂ